Local electric field screening in bi-layer graphene devices - Panchal, Vishal; Giusca, Cristina; Lartsev, Arseniy; Yakimova, Rositsa; Kazakova, Olga (Frontiers in Physics, 2014)
We present experimental studies of both local and macroscopic electrical effects in uniform single- (1LG) and bi-layer graphene (2LG) devices as well as in devices with non-uniform graphene coverage, under ambient conditions. DC transport measurements on sub-micron scale Hall bar devices were used to show a linear rise in carrier density with increasing amounts of 2LG coverage. Electrical scanning gate microscopy was used to locally top gate uniform and non-uniform devices in order to observe the effect of local electrical gating. We experimentally show a significant level of electric field screening by 2LG. We demonstrate that SGM technique is an extremely useful research tool for studies of local screening effects, which provides a complementary view on phenomena that are usually considered only within a macroscopic experimental scheme.